2018
DOI: 10.1111/scs.12641
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle factors, self‐reported health and sense of coherence among fathers/partners in relation to risk for depression and anxiety in early pregnancy

Abstract: Background Father's health is important for mothers and unborn/newborn children and knowledge about expectant fathers’ health in relation to lifestyle and psychosocial aspects is essential. Aims To determine sociodemographic and lifestyle factors, self‐reported health and sense of coherence among fathers and partners in relation to their risk for depression and anxiety in early pregnancy. Methods A cross‐sectional design, descriptive statistics, chi‐squared analysis, T‐test, binary logistic regression, multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 30 publications
(59 reference statements)
3
15
0
1
Order By: Relevance
“…Persson and Kvist 12 showed a correlation between high levels of anxiety and increased risk for depression for both mother and father. An earlier publication, from the same project as the present study, showed that about one in ten prospective fathers/ partners reported a high risk for depression and almost 9% had high anxiety in early pregnancy 13 . Sleeping difficulties and life-style factors such as smoking and the hazardous use of alcohol were reported in that study as determinants for risk for depression, as were socioeconomic factors such as being in financial distress and being unemployed 13 .…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…Persson and Kvist 12 showed a correlation between high levels of anxiety and increased risk for depression for both mother and father. An earlier publication, from the same project as the present study, showed that about one in ten prospective fathers/ partners reported a high risk for depression and almost 9% had high anxiety in early pregnancy 13 . Sleeping difficulties and life-style factors such as smoking and the hazardous use of alcohol were reported in that study as determinants for risk for depression, as were socioeconomic factors such as being in financial distress and being unemployed 13 .…”
Section: Introductionsupporting
confidence: 60%
“…An earlier publication, from the same project as the present study, showed that about one in ten prospective fathers/ partners reported a high risk for depression and almost 9% had high anxiety in early pregnancy 13 . Sleeping difficulties and life-style factors such as smoking and the hazardous use of alcohol were reported in that study as determinants for risk for depression, as were socioeconomic factors such as being in financial distress and being unemployed 13 . It has been shown that a low Sense of Coherence (SOC), which reflects a coping capacity of individuals to deal with everyday life stressors during pregnancy, also increases the risk for depression during the perinatal period [13][14][15] .…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Furthermore, in reviewing vulnerable life phases, such as prenatal and postpartum periods, Finnbogadottir and Perrson (2019) demonstrated the association between lower levels of SOC and a higher risk of depression among expectant fathers.…”
Section: Family Climate Factorsmentioning
confidence: 99%
“…A previous study showed that there is a clear correlation between fathers' depression score and attitudes about participating in parenting (Nath et al, 2015); thus, encouraging fathers to adapt to the paternal role prior to childbirth may prove to be beneficial after childbirth. Stress from gender‐based division of roles, discrepancy between the actual and expected roles related to pregnancy and childbirth, marital relationship, lack of knowledge regarding pregnancy and childbirth, poor self‐esteem, and poor awareness of parenting skills have been shown to be the risk factors of postnatal depression specific to fathers (Bruno et al, 2020; Carlberg et al, 2018; Chhabra et al, 2020; de Cock et al, 2017; Finnbogadóttir & Persson 2019). Furthermore, the association between relationship dissatisfaction and parenting burden, stress, and challenges seems to be bidirectional (Figueiredo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%